Original paperAnalysis of concentration of adhesion molecules ICAM-1 and VCAM-1 in infants and young children with wheezy bronchitis - Gąsiorowska, Joanna; Czerwionka-Szaflarska, Mieczysława; Swincow, Grażyna; Stefańska, Anna; Odrowąż-Sypniewska, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Respiratory infections are among the most frequent causes of visits to general practice and hospitalization in infants and young children. Wheezy bronchitis is diagnosed in majority of them. The most frequent cause of wheezy bronchitis is viral infection. Some children suffer from recurrent bronchitis. In differential diagnosis we should consider chronic diseases, especially bronchial asthma. Inflammation causes that many cells are activated and flow to the place of inflammation by the activation of adhesive molecules. Aim : To assess the concentration of soluble fractions of ICAM-1 and VCAM-1 in serum in infants and young children in the course of wheezy bronchitis. Material and methods : Fifty-four patients with wheezy bronchitis (group I): 32 with the first bronchitis (group IA) and 22 patients with recurrent bronchitis (at least the third one – group IB) were included in the study. The control group (group II) consisted of 26 patients hospitalized due to other causes and without bronchitis in the past. Patients were from 1 to 36 months of age. Among all patients soluble fractions of ICAM-1 and VCAM-1 were analysed by ELISA tests. Results : Median of concentration of ICAM-1 in group I was 418.65 ng/ml and in group II 430.70 ng/ml and the difference was not statistically significant. Mean concentration of ICAM-1 in the group of patients with the first episode of wheezy bronchitis was 386.10 ng/ml and in the group of patients with recurrent bronchitis was 443.50 ng/ml and the difference was not statistically significant. Median concentration of VCAM-1 in group I was 1472.5 ng/ml and in group II 1552.5 ng/ml and the difference was not statistically significant. Mean concentration of VCAM-1 in the group of patients with the first episode of wheezy bronchitis was 1632.5 ng/ml and in the group of patients with recurrent bronchitis was 1334.0 ng/ml and the difference was not statistically significant. Conclusion : On the ground of our study in infants and young children with wheezy bronchitis we conclude that the analysis of ICAM-1 and VCAM-1 concentrations has little clinical signification.